VENEZUELAN REFUGEES IN BRAZIL: IMPACTS ON PEDAGOGICAL PRACTICES IN BASIC EDUCATION - Lawall da Cruz, Nathália (Revista Gênero e Interdisciplinaridade, 2024)
Venezuela is one of the largest oil-producing countries. Despite this, and because of its sole source of exports, the country has been facing a political, economic, and social crisis since 2013. In the same year, Nicolás Maduro, Chávez’s political successor, rose on the Venezuelan political scene, aggravating the pre-existing turmoil in the country in 2014. In this context, Brazil has felt the direct impacts of the crisis by receiving an intense influx of refugees in the Roraima region. According to UNHCR data, 65,811 people in Brazil qualify as refugees. Given this, Venezuelans face various problems, such as a lack of employment and decent living conditions. However, there is little research on the impact of migration on primary education in Brazil. In this context, this article asks: How does pedagogical adaptation impact the lives of Venezuelan refugee students in Brazil? The hypothesis for the development of the text rests on the argument that pedagogical practices are relevant strategies for integrating Venezuelan students in Brazil. Given that, the difficulties and challenges identified mainly include language, curricular differences between the two countries, and psychosocial aspects. The general aim of the article is to understand the importance of pedagogical adaptation in the lives of Venezuelan refugee students in Brazil in the context of primary education. The methodological framework for achieving the proposed objective is a systematic bibliographical review. In addition to the introduction and concluding remarks, the article consists of three sections with specific goals that help to understand the general purpose. We conclude that pedagogical plans are crucial for developing the learning of Refugee Venezuelan students.